Infant gut microbiome is enriched with Bifidobacterium longumssp. infantis in Old Order Mennonites with traditional farming lifestyle. Issue 11 (14th May 2021) - Seppo, Antti E.; Bu, Kevin; Jumabaeva, Madina; Thakar, Juilee; Choudhury, Rakin A.; Yonemitsu, Chloe; Bode, Lars; Martina, Camille A.; Allen, Maria; Tamburini, Sabrina; Piras, Enrica; Wallach, David S.; et al.
Abstract: Background: Growing up on traditional, single‐family farms is associated with protection against asthma in school age, but the mechanisms against early manifestations of atopic disease are largely unknown. We sought determine the gut microbiome and metabolome composition in rural Old Order Mennonite (OOM) infants at low risk and Rochester, NY urban/suburban infants at high risk for atopic diseases. Methods: In a cohort of 65 OOM and 39 Rochester mother‐infant pairs, 101 infant stool and 61 human milk samples were assessed by 16S rRNA gene sequencing for microbiome composition and qPCR to quantify Bifidobacterium spp. and B . longum ssp. infantis ( B. infantis ), a consumer of human milk oligosaccharides (HMOs). Fatty acids (FAs) were analyzed in 34 stool and human 24 milk samples. Diagnoses and symptoms of atopic diseases by 3 years of age were assessed by telephone. Results: At a median age of 2 months, stool was enriched with Bifidobacteriaceae, Clostridiaceae, and Aerococcaceae in the OOM compared with Rochester infants. B . infantis was more abundant ( p < .001) and prevalent, detected in 70% of OOM compared with 21% of Rochester infants ( p < .001). Stool colonized with B . infantis had higher levels of lactate and several medium‐ to long/odd‐chain FAs. In contrast, paired human milk was enriched with a distinct set of FAs including butyrate. Atopic diseases were reported in 6.5% of OOM and 35% of Rochester children ( p < .001). Conclusion: A high rate of B . infantis colonization, similar to that seen in developing countries, is found in the OOM at low risk for atopic diseases. Abstract : This study investigates the impact of traditional farming lifestyle on infant gut microbiome. Infant stool and milk sample analyses of microbiome composition and fatty acids concentrations were perfomed in a cohort of Old Order Mennonite infants at low risk and Rochester urban/suburban infants at high risk for atopic diseases. Microbiome of Old Order Mennonite infants is enriched in B . infantis compared with Rochester infants, which may be beneficial in prevention of atopic diseases.